(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: teenage pregnancy is a worldwide social problem. The aim of this study is to provide more data for a better understanding of the possible maternal and foetal risks associated with teenage pregnancies. Methods: the hospital records of all pregnant women, aged between 14 and 19, from the obstetric registers of the Policlinico Umberto I Hospital in Rome, between 2000 and 2010, have been completely reviewed (n=184). For each pregnant woman socio-demographic characteristics, obstetric history, pregnancy and birth outcomes were also determined. Our results were compared with a control group composed of 150 primigravida adult women aged 20-29 years who delivered at the Policlinico Umberto I Hospital in Rome in the same period. Results: the mean age ± SD of the study group was 17.9 ± 1.2, while that of the control group was 25.4 ± 2.4. The control group had a significantly lower risk of preterm delivery (p=0.000). The rate of low birth weight babies born to the young mothers was significantly higher than that of babies born to the adult mothers (p=0.036). The study group had a lower risk of instrumental delivery and a higher proportion of spontaneous delivery (p=0.000). Finally, we observed a statistically significant difference of the APGAR score at the fifth minute between the two groups (p=0.004). Conclusions: our results seemed to confirm the outcomes of previous studies for adolescent pregnant women, mainly regarding the increased risks of preterm deliveries and low birth weight babies, the higher incidence of spontaneous vaginal delivery and the lower incidence of instrumental delivery.